Diagnosis of DWI-negative acute ischemic stroke: A meta-analysis. (18th July 2017) - Edlow, Brian L.; Hurwitz, Shelley; Edlow, Jonathan A.
Abstract : Objective: To determine the prevalence of diffusion-weighted imaging (DWI)–negative acute ischemic stroke (AIS) and to identify clinical characteristics of patients with DWI-negative AIS. Methods: We systematically searched PubMed and Ovid/MEDLINE for relevant studies between 1992, the year that the DWI sequence entered clinical practice, and 2016. Studies were included based upon enrollment of consecutive patients presenting with a clinical diagnosis of AIS prior to imaging. Meta-analysis was performed to synthesize study-level data, estimate DWI-negative stroke prevalence, and estimate the odds ratios (ORs) for clinical characteristics associated with DWI-negative stroke. Results: Twelve articles including 3, 236 AIS patients were included. The meta-analytic synthesis yielded a pooled prevalence of DWI-negative AIS of 6.8%, 95% confidence interval (CI) 4.9–9.3. In the 5 studies that reported proportion data for DWI-negative and DWI-positive AIS based on the ischemic vascular territory (n = 1, 023 AIS patients), DWI-negative stroke was strongly associated with posterior circulation ischemia, as determined by clinical diagnosis at hospital discharge or repeat imaging (OR 5.1, 95% CI 2.3–11.6, p < 0.001). Conclusions: A small but significant percentage of patients with AIS have a negative DWI scan. Patients with neurologic deficits consistent with posterior circulation ischemia have 5 times the odds of having a negative DWI scan compared to patients with anterior circulation ischemia. AIS remains a clinical diagnosis and urgent reperfusion therapy should be considered even when an initial DWI scan is negative.